Evolution of mating behavior between two populations adapting to common environmental conditions. Issue 8 (18th March 2015) - Bárbaro, Margarida; Mira, Mário S.; Fragata, Inês; Simões, Pedro; Lima, Margarida; Lopes‐Cunha, Miguel; Kellen, Bárbara; Santos, Josiane; Varela, Susana A. M.; Matos, Margarida; Magalhães, Sara
Abstract: Populations from the same species may be differentiated across contrasting environments, potentially affecting reproductive isolation among them. When such populations meet in a novel common environment, this isolation may be modified by biotic or abiotic factors. Curiously, the latter have been overlooked. We filled this gap by performing experimental evolution of three replicates of two populations of Drosophila subobscura adapting to a common laboratorial environment, and simulated encounters at three time points during this process. Previous studies showed that these populations were highly differentiated for several life‐history traits and chromosomal inversions. First, we show initial differentiation for some mating traits, such as assortative mating and male mating rate, but not others (e.g., female mating latency). Mating frequency increased during experimental evolution in both sets of populations. The assortative mating found in one population remained constant throughout the adaptation process, while disassortative mating of the other population diminished across generations. Additionally, differences in male mating rate were sustained across generations. This study shows that mating behavior evolves rapidly in response to adaptation to a common abiotic environment, although with a complex pattern that does not correspond to the quick convergence seen for life‐history traits. Abstract : In this study, we describe how the mating traits of two differentiated Drosophila subobscura populations evolve during adaptation to a common abiotic environment. We find that, counter‐intuitively, reproductive barriers increase between populations.